The Effect of Managerial Ability on The Performance of Islamic Religious College Lecturers - Nasution, Melda Diana; Afandi, Faisal (JURNAL AL-TANZIM, 2022)
This study aims to determine the effect of managerial leadership abilities on the performance of lecturers at the Islamic Religious College in Padangsidimpuan. The type of research used in this research is correlational research. The results showed a significant and positive effect of the leadership's managerial ability on the lecturer's performance at the Islamic Religious College (PTKI) in Padangsidimpuan, with a moderate strength of 0.498. This value indicates a relatively low positive relationship, meaning a unidirectional relationship between the X variable and the Y variable. The contribution given by managerial ability is 24.8%. This shows that the leadership's managerial ability will improve the lecturer performance of lecturers and other staff support it. The implications of the results of this study can be used as input for PTKI leaders and lecturers, in improving organizational governance and performance, for the realization of a superior PTKI.